The Nexus Between Live-Streaming Commerce, Engagement and Purchase Intention - Liu, Yang; Edu , Tudor (Transformations In Business & Economics, 2025)
Live-streaming commerce (LSC), as the latest form of e-commerce, is experiencing significant growth. Based on the SOR theory, this research proposes a model on the influence of LSC’s space and atmosphere characteristics on telepresence (TLP), social presence (SOP), flow experience (FE), and their influence on engagement (ENG) and purchase intention (PI). Using a non-random sampling technique and an online questionnaire, data were collected from 370 respondents in China. Using PLS-SEM, the results show that visibility and authenticity, as space characteristics, and entertainment and activity, as atmosphere characteristics, had significant positive effects on TLP, SOP and FE, while these variables significantly positively affected ENG and PI. TLP partially mediated the effect of AUT on FE; while ENG, the influence of TLP on PI. Theoretical contributions are made in four areas. Practical implications for LSC businesses and streamers are addressed. Future studies could further test the model and expand it.